2022
DOI: 10.1186/s13014-022-02128-w
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy versus conventional radiotherapy for painful bone metastases: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background Stereotactic body radiotherapy (SBRT) is a promising approach in treating painful bone metastases. However, the superiority of SBRT over conventional external beam radiotherapy (cEBRT) remains controversial. Therefore, this systematic review and meta-analysis of randomised controlled trials was conducted to compare SBRT and cEBRT for the treatment of bone metastases. Methods A search was conducted using PubMed on January 22, 2022, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Results and conclusions gleaned from systematic reviews and meta-analyses of SBRT versus conventional radiotherapy for symptomatic bone metastases are conflicting [ 35 37 ]. Four such meta-analyses consider the combination of spine and non-spine sites.…”
Section: Sbrt For Symptomatic Bone Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results and conclusions gleaned from systematic reviews and meta-analyses of SBRT versus conventional radiotherapy for symptomatic bone metastases are conflicting [ 35 37 ]. Four such meta-analyses consider the combination of spine and non-spine sites.…”
Section: Sbrt For Symptomatic Bone Metastasesmentioning
confidence: 99%
“…Four such meta-analyses consider the combination of spine and non-spine sites. Ito et al’s meta-analysis demonstrated no statistical difference between conventional and SBRT for overall pain response, adverse events, quality of life or overall survival [ 35 ]. In contrast, Lee et al’s meta-analysis demonstrated that SBRT reduced rates of progression, improved complete pain response rates at 3 months, and increases the likelihood of pain flares [ 36 ].…”
Section: Sbrt For Symptomatic Bone Metastasesmentioning
confidence: 99%
“…Since 2019, conflicting results from RCTs and comparative studies on pain response have been published . To aggregate the results of these newer studies, several meta-analyses assessed pain response for metastatic bone disease and again published conflicting conclusions . In our review, we included the largest RCT to our knowledge and an eighth RCT on this subject .…”
Section: Introductionmentioning
confidence: 99%
“…Extreme hypofractionation cuts treatment duration into a fraction of what is needed to complete traditional regimens, e.g. 3 Gy × 10 [ 6 ]. As suggested by a recent large meta-analysis [ 7 ], there is room for improvement of physicians’ prescription habits or ability to decipher prognosis, because the authors found that 16% of patients with advanced cancer receiving palliative radiotherapy died within 30 days of treatment.…”
Section: Introductionmentioning
confidence: 99%